How to leverage a strong brand to retain trust: two case studies - Lauterborn, Robert F. (Henry Stewart Talks, 2017)
This case study examines Johnson & Johnson’s behaviour during the Tylenol poison scandal of 1982. In pulling all potentially contaminated products from the shelves, Johnson & Johnson retained consumer trust and thus remained the number one brand in the industry. In contrast Union Carbide avoided taking responsibility for the Bhopal disaster and trust in their brand was destroyed as a result.